2021
DOI: 10.3389/fped.2021.753708
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Children With Extracorporeal Membrane Oxygenation in a Developing Country: An 11-Year Single-Center Experience

Abstract: Introduction: Extracorporeal Membrane Oxygenation (ECMO) is a lifesaving procedure for patients with refractory cardiac or respiratory failure. The indications for ECMO are growing, and it is increasingly being used to support cardiopulmonary failure in children. However, the risks and benefits of ECMO should be weighed before deploying it on the patients. The objectives of this study were to identify the mortality risk factors and to determine the ECMO outcomes.Methods: The retrospective chart reviews were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…No randomized clinical trials were identified in this literature search. Studies did not always specify where the samples were obtained, but seven studies specified the PICU (2, 8, 13, 18, 19, 21, 22). Five studies were conducted in The Netherlands (12, 17, 19, 20, 24), four studies in the United States (9, 13, 18, 23), two studies in Spain (2, 21), one study in Singapore (8), one study in China (25), and one study in Thailand (22).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…No randomized clinical trials were identified in this literature search. Studies did not always specify where the samples were obtained, but seven studies specified the PICU (2, 8, 13, 18, 19, 21, 22). Five studies were conducted in The Netherlands (12, 17, 19, 20, 24), four studies in the United States (9, 13, 18, 23), two studies in Spain (2, 21), one study in Singapore (8), one study in China (25), and one study in Thailand (22).…”
Section: Methodsmentioning
confidence: 99%
“…In the five studies that listed sex, both males and females were represented evenly (8, 9, 13, 17, 23, 24). Neonatal pulmonary and cardiac diseases were the greatest underlying diagnoses requiring ECMO (2, 8, 9, 12, 17–25). Four studies evaluated patients who only received EN (9, 12, 13, 20).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations